Nutritional Knowledge and Attitudes of Adolescent Swimmers in Trinidad and Tobago - Marquitta C. Webb; Safiya E. Beckford (Journal of Nutrition and Metabolism)
Purpose. To investigate the level of nutrition knowledge and attitude of adolescent male and female swimmers training competitively in Trinidad and Tobago. Methodology. A self-administered questionnaire, which consisted of 21 nutrition knowledge and 11 attitude statements, was utilized to assess the level of nutrition knowledge and attitude of adolescent swimmers. For the assessment of nutrition knowledge, correct answers were given a score of “1” and incorrect answers were given a score of “0.” For the evaluation of attitude towards nutrition, a score ranging from 1 to 5 was assigned to each response; “5” was given to the most positive response, and “1” was given to the most negative. Data were analyzed using SPSS version 21.0. Results. Two hundred and twenty swimmers with a mean age of 14.56±2.544 completed the questionnaire. The mean nutrition knowledge score was 10.97±2.897 and mean attitude score was 41.69±6.215. Nutrition knowledge was positively and significantly related to the number of reported nutrition sources (r=0.172, P=0.005). Nutrition knowledge was positively and significantly related to the attitude (r=0.130, P=0.027). Conclusions and Implication. Athletes lack nutrition knowledge but have a positive attitude towards nutrition, which may indicate receptiveness to future nutrition education.